2016
DOI: 10.1021/acs.est.6b04076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Thyroidogenic Effects of Diuron and Its Metabolite 3,4-DCA in Tadpoles of the American Bullfrog (Lithobates catesbeianus)

Abstract: Temperature is a key variable affecting the timing of amphibian metamorphosis from tadpoles to tetrapods, through the production and subsequent function of thyroid hormones (TH). Thyroid function can be impaired by environmental contaminants as well as temperature. Tadpoles can experience large temperature fluctuations in their habitats and many species are distributed in areas that may be impacted by agriculture. Diuron is a widely used herbicide detected in freshwater ecosystems and may impact endocrine func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The temperature of the tanks and individual aquariums had their values recorded daily to observe possible variations during the experimental period. Temperature values used in this study were based on Freitas et al (2016), which recorded the water temperature in 5 natural ponds in which tadpoles of R. schneideri and P. nattereri are frequently found. These data were recorded during the summer, which coincides with the rainy season and reproduction for most neotropical frogs.…”
Section: Temperature Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature of the tanks and individual aquariums had their values recorded daily to observe possible variations during the experimental period. Temperature values used in this study were based on Freitas et al (2016), which recorded the water temperature in 5 natural ponds in which tadpoles of R. schneideri and P. nattereri are frequently found. These data were recorded during the summer, which coincides with the rainy season and reproduction for most neotropical frogs.…”
Section: Temperature Treatmentmentioning
confidence: 99%
“…Due to the small volume of water in ephemeral ponds, the water temperature is easily elevated, increasing the average temperatures and the daily thermal fluctuations. Previous studies have shown that the water temperature can exceed 40°C during the summer in ponds where several species of tadpoles have been found in Brazil (Freitas et al, 2016). The deforestation in nearby areas of amphibian habitats and the loss of vegetation has also favored the increase of solar incidence in these small ponds, thus contributing to the water heating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding endocrine responses, the anti-estrogenic activity of irgarol was reported using a yeastbased in vitro assay (Westlund and Yargeau, 2017). Recent studies demonstrate that the antifouling booster diuron, which also acts in PSII, affect the thyroid system, growth, and development of aquatic organisms, including tadpoles American bullfrog Lithobates catesbeianus and the estuarine fish Menidia beryllina (Freitas et al, 2016;Moreira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%